2014
DOI: 10.3390/rs6032176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potentials of Sentinel-2 for Archaeological Perspective

Abstract: Abstract:The potentials of the forthcoming new European Space Agency's (ESA) satellite sensor, Sentinel-2, for archaeological studies was examined in this paper. For this reason, an extensive spectral library of crop marks, acquired through numerous spectroradiometric campaigns, which are related with buried archaeological remains, has been resampled to the spectral characteristics of Sentinel-2. In addition, other existing satellite sensors have been also evaluated (Landsat 5 Thematic Mapper (TM); Advanced Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 52 publications
2
51
0
1
Order By: Relevance
“…Although some fusion techniques already exist, like pan-sharpening between multi-spectral and panchromatic bands of the same or different satellite sensors [26,27], or as more recently shown, fusion between archive greyscale and recent multispectral satellite images [28], fusion methodologies of more diverse datasets need to be developed and tested for archaeological research. Studies have shown that it is feasible to scale-up ground spectroradiometric data (i.e., ground spectral signatures) to existing [29] or even forthcoming satellite sensors [30].…”
Section: Methodsmentioning
confidence: 99%
“…Although some fusion techniques already exist, like pan-sharpening between multi-spectral and panchromatic bands of the same or different satellite sensors [26,27], or as more recently shown, fusion between archive greyscale and recent multispectral satellite images [28], fusion methodologies of more diverse datasets need to be developed and tested for archaeological research. Studies have shown that it is feasible to scale-up ground spectroradiometric data (i.e., ground spectral signatures) to existing [29] or even forthcoming satellite sensors [30].…”
Section: Methodsmentioning
confidence: 99%
“…The usefulness of medium and high-resolution satellite data is well established and the procedures for the identification of buried structures are well described in Earth observation studies applied to cultural heritage and aerial archaeology [7,41,48]. In particular, the presence of buried structures or anthropogenic transformation with high impact on the landscape (ditches, trenches, etc.)…”
Section: Sentinel-2 Datamentioning
confidence: 99%
“…This activity resulted in several experiments based on simulated S2 datasets [5][6][7][8][9][10][11][12][13][14][15]. These studies reported a high potential of S2 in various fields of application.…”
Section: Introductionmentioning
confidence: 99%